Stoma Retraction in Super-Morbidly Obese Patient Leading to Class IV Midline Wound: A Cautionary Tale - Ryan D Morgan BS; Albin John MBA; Brandon Youssi BS; Shirley McReynolds FNP-C; Yana Puckett MD; Catherine Ronaghan MD (SAGE Publishing, 2022)
Stoma creation is often necessary for fecal diversion in general surgery. The creation of stomas involves mobilization of either the large or small intestine through the abdominal wall to allow for the passage of waste that traverses the intestinal tract. Among the complications of stoma creation, particularly in obese patients, is stoma retraction, whereby the stoma retracts greater than 5 mm from the skin. This is often accompanied by extensive dermal dehiscence, which can lead to significant leakage resulting in infection. Here, we present the case of a super-morbidly obese female patient with an end ileostomy following total colectomy in which abdominal closure was not initially achieved. The stoma became retracted and dehisced leading to continued contamination of the open abdomen, necessitating multiple abdominal washouts. Injection of 300 units of botulinum toxin A (BTA) was administered into the abdominal wall muscles later the day of her index operation. An Abdominal Wall Reapproximation Anchor (ABRA) dynamic tissue system (DTS) was utilized successfully in subsequent operations for primary myofascial closure. Heavy continuous contamination of the midline wound through the subcutaneous cleft between the retracted ileostomy and midline surgical wound was treated with intensive wound care, strict bed rest, nothing to eat or drink (NPO), and total parenteral nutrition (TPN). Post-operative stoma complications occur frequently, and stoma retraction is commonly encountered, especially in the obese. The patient presented in this case study had multiple risk factors which led to a complicated treatment course. Successful primary myofascial closure and complete healing of the midline surgical wound highlights the importance of a patient-tailored multimodal approach.